2019
DOI: 10.1371/journal.pone.0214066
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antibacterial and anticancer properties of Se-NPs decorated TiO2 nanotube film

Abstract: Selenium nanoparticle modified surfaces attract increasing attention in the field of tissue engineering. Selenium exhibits strong anticancer, antibacterial and anti-inflammatory properties and it maintains relatively low off-target cytotoxicity. In our paper, we present the fabrication, characterization and cytocompatibility of titanium oxide (TiO2) nanotube surface decorated with various surface densities of chemically synthesized selenium nanoparticles. To evaluate antibacterial and anti-cancer properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 47 publications
4
23
0
Order By: Relevance
“…Similarly, as depicted by Perni et al, when the totality of the paraben is released from HA, but only about 5% of the initial amount of propylparaben is released from PMMA. 44 Furthermore, the percentage of the released selenium proportionally increased with increasing surface density of nanoparticles as in research done by Bilek et al 45 For instance, after 4 days, the SeNPs release from 15PC-SeNPs-TCP began to improve by 97.46 ppb when compared to (Figure 9), the numbers of viable E. coli bacteria on the surfaces of the TCP, especially on 15TCP, significantly reduced with respect to PMMA. The bacterial count for PMMA was found to be 34.2 CFU.10 5 mL À1 , when for 15PC-SeNPs-TCP was 0.2 CFU.10 5 mL À1 (p < 0.005).…”
Section: Selenium Release From Bone Cementssupporting
confidence: 54%
See 1 more Smart Citation
“…Similarly, as depicted by Perni et al, when the totality of the paraben is released from HA, but only about 5% of the initial amount of propylparaben is released from PMMA. 44 Furthermore, the percentage of the released selenium proportionally increased with increasing surface density of nanoparticles as in research done by Bilek et al 45 For instance, after 4 days, the SeNPs release from 15PC-SeNPs-TCP began to improve by 97.46 ppb when compared to (Figure 9), the numbers of viable E. coli bacteria on the surfaces of the TCP, especially on 15TCP, significantly reduced with respect to PMMA. The bacterial count for PMMA was found to be 34.2 CFU.10 5 mL À1 , when for 15PC-SeNPs-TCP was 0.2 CFU.10 5 mL À1 (p < 0.005).…”
Section: Selenium Release From Bone Cementssupporting
confidence: 54%
“…44 Furthermore, the percentage of the released selenium proportionally increased with increasing surface density of nanoparticles as in research done by Bilek et al. 45 For instance, after 4 days, the SeNPs release from 15PC-SeNPs-TCP began to improve by 97.46 ppb when compared to 25.82 ppb from 2.5PC-SeNPs-TCP. Similarly, released selenium at the end of 3 days was 18.8 ppb for 2.5PC-SeNPs-PMMA when 121 ppb for 15PC-SeNPs-PMMA.…”
Section: Resultsmentioning
confidence: 64%
“…Among them, selenium nanoparticles (SeNPs) have attracted increased attention. Selenium (Se) is an essential trace element for humans (about 50 µg/day), and antimicrobial studies using different forms of Se, such as selenite and SeNPs, have been reported [28][29][30][31][32][33]. Se is a significant element, because it is an important cofactor for antioxidant enzymes such as glutathione peroxidase and thioredoxin reductase [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…TiNTs have potential applications in several fields; they are found in biomaterials, gas sensors, adsorbents, heterogeneous catalysis ( photocatalysis, oxidation reactions, organic synthesis, biomass,…), biological activities to remove bacteria from water, solar cells, Li battery production, and many others. In particular, TiNTs have been used as a catalytic support for different active species (metals, oxides and sulfides).…”
Section: Introductionmentioning
confidence: 99%